2004
DOI: 10.1099/ijs.0.02951-0
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia unamae sp. nov., an N2-fixing rhizospheric and endophytic species

Abstract: It was shown recently that the genus Burkholderia is rich in N2-fixing bacteria that are associated with plants. A group of these diazotrophic isolates with identical or very similar 16S rDNA restriction patterns [designated amplified rDNA restriction analysis (ARDRA) genotypes 13, 14 and 15] was selected and a polyphasic taxonomic study was performed, which included new isolates that were recovered from rhizospheres, rhizoplanes or internal tissues of maize, sugarcane and coffee plants. Morphological, physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(111 citation statements)
references
References 28 publications
(26 reference statements)
7
93
0
11
Order By: Relevance
“…Van Borm et al, (2002) recently showed that the micro flora inhabiting a pouch shaped organ at the junction of the midgut and the intestine of Tetraponera ants partially consists of Burkholderia species, which are most likely involved in the oxidative recycling of nitrogen rich waste. Growth and acetylene reduction was observed in B. unamae with different carbon sources in N-free semi solid BAz (Caballero-Mellado et al, 2004). In the present experiment, acetylene reduction assay in the isolates revealed that all the isolates showed nitrogenase activity and nitrogen fixation.…”
Section: Root Lengthmentioning
confidence: 61%
“…Van Borm et al, (2002) recently showed that the micro flora inhabiting a pouch shaped organ at the junction of the midgut and the intestine of Tetraponera ants partially consists of Burkholderia species, which are most likely involved in the oxidative recycling of nitrogen rich waste. Growth and acetylene reduction was observed in B. unamae with different carbon sources in N-free semi solid BAz (Caballero-Mellado et al, 2004). In the present experiment, acetylene reduction assay in the isolates revealed that all the isolates showed nitrogenase activity and nitrogen fixation.…”
Section: Root Lengthmentioning
confidence: 61%
“…We checked by 16S rDNA sequences in 4 species but we did not sequence one isolate (G4.2), because in term of colony and substrate utilization of G4.1 and G4.2 isolates were similar. Fatty acid methyl ester profiles of strains C13.1, G4.1, G5.1 and G5.2 were compared with those of related Burkholderia species such us B. sacchari 4) , B. pyrrocinia 32) , B. terricola 11) , B. nodosa 6) , B. ferrariae 38) , B. unamae 5) and B. kururiensis 44) . The fatty acid profiles of strains C13.1, G4.1 and G5.1 were similar to those of B. sacchari, B. pyrrocinia and B. terricola, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Burkholderia unamae represent an example of adapted bacteria with potential as PGPB to be applied in Mexican fields. B. unamae has the potential to fix nitrogen, produce phytohormones, siderophores and other inhibitory substances, ACC‐deaminase activity and degradation of toxic aromatic compounds (Caballero‐Mellado et al ., 2004, 2007; Onofre‐Lemus et al ., 2009). Nevertheless, as we mention before, effective bacteria for the crop field will be those able to express the genes responsible of the plant growth promotion or bioremediation in association with plants under real environmental conditions.…”
mentioning
confidence: 99%